The Construction of Collaborative Governance Mechanisms for Green Space in Megacities: Evidence from China - Sailiu Miao; Hong Tan (SAGE Open)
As urbanization accelerates, the collaborative governance of green spaces has become a critical issue for megacities seeking sustainable development. Most existing studies focus on the successful experiences of Western democracies, and there is a lack of systematic discussion on the collaborative dynamics and practices under different political systems. This paper develops a theoretical framework based on grounded theory to analyze the collaborative governance of green spaces in Chinese megacities and reveals its key dynamics. The findings indicate that principled engagement, shared motivation, and capacity for joint action are essential drivers contributing to collaborative governance in China. In a centralized system, the government achieves efficient governance through specific screening mechanisms, top-down political pressure, strong leadership and resource integration capabilities. This study provides a robust theoretical framework and empirical insights into centralized collaborative governance, offering references to the Chinese experience in enhancing the effectiveness of green space governance in global megacities.